Effect of bovine bone morphogenetic proteins on radius fracture healing in rabbits - Lima,Alfredo Feio da Maia (2007)
PURPOSE: To investigate the effect of bovine bone morphogenetic proteins (bBMPs) bound to hydroxyapatite plus collagen in the healing of unstable radius fractures. METHODS: A transverse fracture was induced at the mid of the diaphysis in both radii on 15 Norfolk rabbits with average age of 5.5 months and 3.5kg. A mixture of bBMPs bound to thin powdered hydroxyapatite (bBMP-HA) and bovine collagen as agglutinant was applied to the right radius fracture site. The left radius fracture was considered control and no treatment was used. After 30, 60 and 90 days (5 rabbits/period) the rabbits were euthanized and the radii were collected for histological analysis. RESULTS: The descriptive histological analysis revealed that repair was similar for both forelimbs. The histomorphometric analysis showed that the mean area of newly formed bone was 867442.16 mm², 938743.00 mm² and 779621.06 mm² for the control forelimbs, and 841118.47 mm², 788038.76mm² and 618587.24 mm² for the treated forelimbs at 30, 60 and 90 days, respectively. Thus the newly formed bone area was 12.17% larger in the forelimbs treated with bBMP-HA/collagen than in the control forelimbs (p<0.05, Tukey test) in the 60-day period after surgery. In both forelimbs the newly formed bone area increased throughout the experimental period until the complete fracture healing. CONCLUSION: Based on the result obtained here we concluded that bBMP-HA/collagen induced a lower but significant improvement in fracture consolidation.